Effects of climate warming on animals and their regulation of temperature - Yu, Jiarui (Transactions on Environment, Energy and Earth Sciences, 2024)
Warming is the biggest and most serious of the environmental problems of the day, and it’s a matter of survival for living things. Warming is causing metabolic disorders, oxidative stress, immunosuppression and even death in animals. In order to survive, animals have to learn to adapt to climate change, which can be reflected in behavioural and physiological changes, such as early migration of birds, changes in habitat location in response to temperature changes in metazoans, and even modulation of their liver size, corticosterone secretion and maternal effects).